Estereotipos sobre los Roles de Género en Estudiantes del Programa de Psicología de la Universidad Antonio Nariño, Sede Riohacha, La Guajira. (2023)
The main objective of this research was to analyze the Stereotypes and gender roles existing at the Antonio Nariño University, Riohacha campus, specifically in the students of the psychology program. This research has a quantitative, descriptive approach, in a nonexperimental design and therefore the instrument used in this research was the scale of gender stereotypes, which was built considering the theoretical framework on gender studies and related research by (Rocha and Diaz Loving, 2005; Castro and Casique, 2010), on which 5 dimensions were based where the maternity/paternity roles were evaluated; femininity/masculinity¸ skills and abilities, sexuality and expressions of emotion/aggression